Linguistic Landscape and Multicultural Dynamics in Pekanbaru: An Analysis of Culinary Business Names - Erdayani, Rizki; Budiarti, Dian; Firnadia, Evia (ITScience (Information Technology and Science), 2025)
Pekanbaru is one of Indonesia's urban areas inhabited by people from various ethnic and cultural backgrounds. This diversity is manifest in the linguistic landscape, particularly in the nomenclature of culinary enterprises. The objective of this study is to examine the use of language in culinary business names in the city of Pekanbaru using the Linguistic Landscape (LL) approach, from two fundamental functional perspectives: informational function and symbolic function. This study utilizes a qualitative research method characterized by a descriptive approach. The data was collected through a search of the